Congenital Hypoproconvertinemia A Report on 12 Cases with Total Deficiency and 19 Cases with Partial Deficiency - Voss, Dieter; Waaler, Bjarne A (Thrombosis and Haemostasis, 1959)
Investigations on 12 patients with a total and 19 patients with a partial deficiency of proconvertin (factor VII) are reported. All patients proved to have the same deficiency and it was distinguishable from Stuart-Prower factor deficiency. The differentiation between proconvertin deficiency and Stuart-Prower factor deficiency is discussed.